Food Security Outcomes of Indonesia’s Non-Cash Food Assistance Program (BPNT) among Lowest-Expenditure Households - Kharisma, Bayu; Wardhana, Adhitya; Remi, Sutyastie Soemitro; Fathimah, Devi Irmayanti (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study provides the first scientific analysis of the effect of the Non-Cash Food Assistance (BPNT) Program on household food security among Indonesia’s lowest 20% expenditure group. Research Objectives: This study examines the impact of the Non-Cash Food Assistance Program (BPNT) on household food security in Indonesia, with a focus on households in the lowest 20% expenditure group. Research Methods: This study employs a multinomial logistic regression model to investigate the key determinants of food security among households. Empirical Results: The Non-Cash Food Assistance Program (BPNT) plays a significant role in improving the food security of recipient households. Social assistance programs like BPNT can help low-income families by mitigating the negative effects of food price shocks, specifically by promoting dietary diversity. Implications: The government should continually update data to enhance the effectiveness of BPNT distribution, particularly for the poorest 20% of households, who are most vulnerable to food insecurity. It also needs to conduct regular outreach and monitoring to ensure beneficiaries use BPNT properly. JEL Classification: O01, O02, Q0, Q12, Q18 How to Cite:Kharisma, B., Wardhana, A., Remi, S. S., & Fathimah, D. I. (2025). Food Security Outcomes of Indonesia’s Non-Cash Assistance Program (BNPT) among Lowest-Expenditure Households. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 373-390. https://doi.org/10.15408/sjie.v14i2.46203.